The Influence Of Work–Life Balance On Employee Performance Among Working Mothers Pursuing Postgraduate Education: The Moderating Role Of Organizational Support And Social Support - Evadya Khairunnisa; Rayi Dwipanilih; Osly Usman (Journal of Management, Economic, and Accounting, 2026)
The participation of women in the workforce, combined with their roles as mothers and postgraduate students, gives rise to a triple-burden phenomenon that depletes personal resources. This study examines the effect of work-life balance on employee performance, as well as the moderating roles of organizational support and social support, among full-time working women pursuing postgraduate education in the Greater Jakarta area. A quantitative approach was employed through a survey of 100 respondents selected using purposive sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS software. The results indicate that work-life balance has a positive and significant effect on employee performance. Both organizational support and social support strengthen this effect as moderating variables. These findings reinforce the proposition of Conservation of Resources Theory that the availability and accumulation of resources contribute to the performance of individuals facing multiple role demands. This study offers practical implications for organizations to develop family-friendly and education-friendly policies.